Relevantiškumo sąvokos raida - Jurevičiūtė, Regina (Knygotyra, 1986)
Relevance is one of the most fundamental concepts encountered in the theory of information retrieval. The article reviews the evolution of relevance notion till 1970.The early pioneers of information science quite correctly recognized that not all that would be retrieved would be relevant. So the problem of relevance became urgent and the first challenge began. Theoretical works on relevance have resulted in drawing methods and results from other and more vigorous subjects to the study of relevance. Numerous definitions of relevance were offered. The hypotheses by large concentrated on enumerating and classifying the factors that affected relevance judgement, on subjectivity and objectivity of relevance. Specialized experiments on relevance were carried out. In bibliometrics some laws have been uncovered, quantitative observations have been made. Some different views on relevance have been formed.